2017
DOI: 10.3389/fmicb.2017.01061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Risk Factors of Carbapenem-Resistant Klebsiella pneumoniae Infections in Eastern China

Abstract: Background: The increasing prevalence of carbapenem-resistant Klebsiella pneumoniae (CRKP) poses an immediate threat to treatment worldwide. This retrospective study assessed the molecular epidemiology and determined the risk factors for and outcomes of CRKP infections in a general teaching hospital in Shanghai, China.Methods: From January 2013 to July 2015, 100 consecutive unique CRKP isolates isolated from hospitalized patients were collected. Isolates were screened for antibiotic resistance genes by polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
4
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 52 publications
7
40
4
1
Order By: Relevance
“…In this present study, the incidence of MDRIs in the three PICUs was 8.72% (79/906), which is significantly lower than that of previous reports with incidence of MDRIs ranging from 10 to 25% in PICU [9,10]. Previous studies [17][18][19] have reported that the patients with MDRI were hospitalized and treated in the ICU for considerably longer stay and had lower survival rates compared to other patient groups.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In this present study, the incidence of MDRIs in the three PICUs was 8.72% (79/906), which is significantly lower than that of previous reports with incidence of MDRIs ranging from 10 to 25% in PICU [9,10]. Previous studies [17][18][19] have reported that the patients with MDRI were hospitalized and treated in the ICU for considerably longer stay and had lower survival rates compared to other patient groups.…”
Section: Discussioncontrasting
confidence: 67%
“…Many previous studies [6][7][8] have indicated that the incidence of nosocomial infections caused by antibiotic-resistant organisms is increasing. The prevalence of hospital-acquired or nosocomial infections in pediatric patients ranges from 10 to 25% in PICU [9,10]. Therefore, the control of infection in PICU is very important.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, tigecycline and colistin displayed a considerable activity against such strains where 87.5% and 81.25% of the carbapenemase-positive strains were susceptible to tigecycline and colistin, respectively. These findings are in a range similar to that reported by other investigators (He et al, 2015, andZheng et al, 2017).…”
Section: Characteristics Of the Mdr K Pneumoniae Isolatessupporting
confidence: 92%
“…Yuan et al malignancies, hematopoietic stem cell transplantation, tracheotomy, mechanical ventilation, and indwelling catheters. 5,16,17 In our study, univariate analysis results showed that ICU admission, respiratory disease, cardiovascular disease, nervous system disease, digestive disease, invasive operations, and carbapenem exposure were all risk factors for CRKP BSIs. These results are similar to those of previous studies in other parts of the world.…”
Section: Dovepressmentioning
confidence: 51%